Characteristics of fatal drug overdoses among college age decedents in Tennessee, 2019-2020 - Jessica Korona-Bailey; Sutapa Mukhopadhyay (Elsevier, 2022)
Purpose: College age persons experienced unique disruptions to their regular lives during the COVID-19 pandemic, sometimes resulting in negative coping mechanisms. We examined changes in the number of and characteristics of college age fatal drug overdoses before and during the early COVID-19 pandemic. Methods: We conducted a statewide cross-sectional study to determine the changes in the number and characteristics of college age fatal drug overdose decedents before and during the COVID-19 pandemic using 2019-2020 data from the Tennessee State Unintentional Drug Overdose Reporting System. We defined college age as 18-24 years. Frequencies and rates were generated to compare demographics, circumstances, and toxicology between 2019 and 2020. Results: From 2019 to 2020, 336 college age persons experienced an unintentional or undetermined fatal drug overdose in Tennessee. Characteristics of college age decedents: mean age 21.7 years, 68.5% males, and 71.4% White. Rates of fatal overdoses among college age persons increased 50.0% overall, 150.1% for female decedents, and 141.7% for Black decedents. Fewer people were treated for substance use disorder or mental health conditions (p = 0.0243) in 2020. Conclusion: This analysis can inform local and regional public health workers to implement focused prevention and intervention efforts to curtail the overdose epidemic among college age persons in Tennessee.